PENGARUH PEMBERIAN SEDUHAN DAUN BELIMBING WULUH (Averrhoa bilimbi L.) TERHADAP PENURUNAN KADAR GLUKOSA DARAH PADA MENCIT (Mus musculus) DIABETES MELITUS - Santi, Resy Maya; Ansharullah, Ansharullah; Jufri, Nurnashriana (Jurnal Gizi dan Pangan Soedirman, 2025)
Diabetes mellitus (DM) is a non – communicable disease due to hyperglycemia, impaired insulin secrection, or impaired insulin performance. The purpose of this study was to determine whether the steeping of star fruit leaves (Averrhoa bilimbi L.) affects lowering blood glucose levels. This type of research is an experiment groups. This study used 30 mice weighing 20-30 grams, 8 weeks old, divided into 5 groups, namely negative and positive controls, as well as treatment groups with doses 250, 500, and 500 mg/kg BW, with a period of intervention for 14 days through given oral. Statistical analysis was performed using the Paired T-test, One-Way ANOVA test, and Post Hoc LSD test. The results of the Paired T-test test showed a significant value in the opposing group, doses of 250 mg/kg BW, 500 mg/kg BW, and 750 mg/kg BW of 0,000 (p<0,05). The One-Way ANOVA test showed a significant value of 0,000 (p<0,05) which means there is a significant difference in the decrease in blood glucose levels, that the Post Hoc LSD test showed that the treatment group with a dose of 250, 500, and 750 mg/kg BW was effective in reducing fasting blood glucose levels by showing a significant difference of 0,000 (p<0,05). These results indicate that there is an effecf of decreasing blood glucose levels on the 25th day in the treatment group given steeped bean leaves.